Rare earth element (REE) concentrations and radiogenic isotopes (Sr-Nd-Hf) retrieved from bulk sediment leachates, and bulk and clay mineralogical signatures from two piston cores recovered in the Canadian Beaufort and Chukchi-Alaskan margins - Charles-Edouard Deschamps; Jean-Carlos Montero-Serrano; Guillaume St-Onge; André Poirier (PANGAEA, 2019)
Rare earth element (REE) concentrations and radiogenic isotopes (Sr-Nd-Hf) retrieved from bulk sediment leachates, together with bulk and clay mineralogical signatures, were studied on two piston cores recovered in the Canadian Beaufort (AMD0214-02PC) and Chukchi-Alaskan (HLY0501-01JPC) margins to investigate changes in the weathering regimes and deep-water circulation during the Holocene.
Supplement to: Deschamps, C-E et al. (2019): Holocene Changes in Deep Water Circulation Inferred From Authigenic Nd and Hf Isotopes in Sediment Records From the Chukchi-Alaskan and Canadian Beaufort Margins. Paleoceanography and Paleoclimatology, 34(7), 1038-1056, https://doi.org/10.1029/2018PA003485